Hippotherapy: quality of life for the elderly on the horse - Lia Mara Wibelinger; Michele Marinho da Silveira (Kairós Gerontologia, 2011)
Hippotherapy is a technique of rehabilitation and education that uses horse riding and equestrian activities to provide physical benefits to the practitioner, psychological, educational and social. This activity requires the participation of the entire body, the practitioner working in a global horse being used as a therapeutic method that will help develop equilibrium, muscle tone, muscle strength, body awareness, improvement of motor coordination, attention, self-confidence, self-esteem and quality of life. Hippotherapy in the elderly will use the horse as a therapeutic agent in treating various pathologies providing welfare and thus improved quality of life, and a pleasurable treatment, because it runs away from offices and indoor environments. Moreover, threedimensional movement, rhythmic rocking horse and will stimulate the vestibular system, the improvement of consciousness space-time, concentration, equilibrium and consolidation of security gravitational leaving the elderly less vulnerable to falls and related disabilities. Therefore, this article literature review aimed to determine the effects and show the importance of the practice of hippotherapy in order to obtain better quality of life and longevity.